Na–K–Li geochemistry of the Prestige pluton in the Slave Province of the Canadian Shield - Kretz, Ralph; Garrett, Diane; Garrett, Robert G. (Canadian Journal of Earth Sciences, 1982)
In the southwestern Slave Province (Canadian Precambrian Shield), a cluster of 14 muscovite–biotite granite plutons dated at about 2.6 × 10 9 years was emplaced into a thick succession of Archean greenstone, graywacke, and argillite known as the Yellowknife Supergroup. One of the medium-sized plutons (the Prestige pluton), with an outcrop area of 14 km 2 , consists of equal portions of quartz, plagioclase, and potash feldspar, and minor muscovite, biotite, and apatite. The presence of muscovite, andalusite, and sillimanite in the metamorphic aureole indicates that the pluton was emplaced at a depth of about 9 km (2.5 kbar (250 MPa)) and a temperature of about 600 °C. The texture is complex, as shown especially by muscovite, which occurs as large crystals, as small oriented inclusions in plagioclase, and as fine-grained aggregates along grain boundaries.The mean density of the Prestige granite is 2.641 g cm −3 , which is less than that of the country rock by a factor of 0.96. The mean alkali content is 2.5 wt.% Na, 4.3 wt.% K, and 700 ppm Li (80 samples). Na and K are normally distributed; Li is strongly skewed. Analysis of variance shows that 50–80% of the element variability occurs on a small scale (within 0.25 km 2 cells). Some of this variability was possibly produced by chemical transport reactions such as:[Formula: see text]which may also account for some of the textural complexity.Large-scale trends within the Prestige pluton could be detected for K and Li but not for Na. Thus the western half is relatively poor in K, and the narrow margin of the pluton is relatively rich in Li. These trends may be attributed to inhomogeneity within the granite prior to emplacement or to a large-scale migration of alkalies that occurred during the formation of the associated pegmatite dikes.Virtually all of the physical and chemical data that are available for the Prestige pluton are consistent with a model that supposes the granite body was in a totally crystalline, but plastic, condition while it migrated to higher ...